Equilibrium Asset Pricing in Directed Networks - Branger, Nicole; Konermann, Patrick; Meinerding, Christoph; Schlag, Christian (Review of Finance, 2021)
Abstract Directed links in cash flow networks affect the cross-section of risk premia through three channels. In a tractable consumption-based equilibrium asset pricing model, we obtain closed-form solutions that disentangle these channels for arbitrary directed networks. First, shocks that can propagate through the economy command a higher market price of risk. Second, shock-receiving assets earn an extra premium since their valuation ratios drop upon shocks in connected assets. Third, a hedge effect pushes risk premia down: when a shock propagates through the economy, an asset that is unconnected becomes relatively more attractive and its valuation ratio increases.